Single-cell profiling of MS CSF B cells highlights roles for TNFα and mTORC1 signalling. Issue 9 (12th August 2022) - Jacobs, Benjamin; Ban, Maria; Baker, Amie; Al-Najjar, Raghda; Else, Jonathan; Sawcer, Stephen
Abstract : The presence of oligoclonal immunoglobulin bands in the cerebrospinal fluid (CSF) has long been rec- ognised as a characteristic manifestation of the immune dysregulation underlying multiple sclerosis (MS). However, it remains unclear how or why these bands develop, and little is known about the nature of the aberrantly expanded B cell clones that produce these immunoglobulins. To explore these questions we have performed single-cell RNA sequencing in CSF (108, 219 cells) and PBMCs (232, 587 cells) obtained from 104 individuals; 66 with multiple sclerosis, 25 with Non-Inflammatory Neurological Conditions (NINCs) and 13 with other Inflammatory Neurological Conditions (INCs). We found that MS CSF harbours an 8-fold higher proportion of plasma cells than control CSF. Plasma cells in the MS CSF up-regulate diverse pathways implicated in pro-inflammatory signalling and antibody synthesis, including TNFα and mTORC1 signalling, compared with their peripheral counterparts.We identified a large number of clonally-expanded cells in the MS CSF which are largely IgG+ plasma cells with evidence of intrathecal antigen experience. These clonally-expanded cells display clonal connections to the periphery. Our findings elucidate the phenotype of a critical cell population in MS biology – clonally-expanded CSF plasma cells. These insights have potential diagnostic and therapeutic implications, and may lead to more general insights into B cell autoimmunity.